Yam seed system characteristics in Nigeria: Local practices, preferences, and the implications for seed system interventions. (December 2021) - Stuart, Esmé; Asfaw, Asrat; Adebola, Patrick; Maroya, Norbert; Edemodu, Alex; Adeosun, Tunde; Asiedu, Robert; Almekinders, Conny
Yam is an important food and cash crop in Nigeria. The seed system is mostly farmer-based and its challenges and opportunities are not well documented. This study reports results of surveys, interviews, focus group discussions and participant observations that describe local practices characterizing yam cultivation and the farmer-based seed system in five states in Nigeria. Our findings show that ware and seed yam are dynamic and highly commercialized goods in Nigeria. There is a high demand for, and a high turn-over of, seed yam. The reasons for the high demand are the low multiplication rate and degeneration of seed yam which lead farmers to frequently acquire fresh seeds and replace varieties, investing significantly in the seed of ware yam. The study found some farmers specializing in seed yam production but less than expected for such a highly commercial crop. The market is the major source for off-farm sourced seed yam, and although completely informal, the seed yam sector is vibrant and well organized. The identification of strategically positioned farmers and traders can offer opportunities and entry points for introduction of new varieties and improved seed production techniques. Building on the existing farmer-based system is a more logical strategy than replacing it with formal structures and legislative regulation.